2008
DOI: 10.1016/j.jmva.2006.11.002
|View full text |Cite
|
Sign up to set email alerts
|

A test for the mean vector with fewer observations than the dimension

Abstract: In this paper, we consider a test for the mean vector of independent and identically distributed multivariate normal random vectors where the dimension p is larger than or equal to the number of observations N. This test is invariant under scalar transformations of each component of the random vector. Theories and simulation results show that the proposed test is superior to other two tests available in the literature. Interest in such significance test for high-dimensional data is motivated by DNA microarrays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
253
0
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 239 publications
(265 citation statements)
references
References 11 publications
4
253
0
1
Order By: Relevance
“…While acknowledging the defect of the Hotelling test, as indicated in [3,16], Srivastava and Du (2008) [42] noted that the NET and ANT are not scale invariant, which may cause lower power when the scales of different components of the model are very different. Accordingly, they proved the following modification to the ANT:…”
Section: Srivastava and Du's Approachmentioning
confidence: 99%
See 2 more Smart Citations
“…While acknowledging the defect of the Hotelling test, as indicated in [3,16], Srivastava and Du (2008) [42] noted that the NET and ANT are not scale invariant, which may cause lower power when the scales of different components of the model are very different. Accordingly, they proved the following modification to the ANT:…”
Section: Srivastava and Du's Approachmentioning
confidence: 99%
“…where λ(R) is the largest eigenvalue of the correlation matrix R. Srivastava and Du [42] showed that if n ≍ p η and 1 2 < η 1,…”
Section: Srivastava and Du's Approachmentioning
confidence: 99%
See 1 more Smart Citation
“…and c q,n = 1 + trR 2 /q 3/2 is an adjustment factor converging to 1 in probability as (n, q) → ∞, n = O(q δ ), δ > 1/2 proposed by Srivastava and Du (2008). Define the population correlation matrix as…”
Section: Test Statistic Based On Trwmentioning
confidence: 99%
“…Srivastava (2007) proposed a Hotelling's T 2 type test, by using Moore-Penrose inverse of the sample covariance matrix instead of the inverse when N is smaller than p. It may be noted that all the above discussed tests are invariant under the group of orthogonal matrices. A test that is invariant under the group of non-singular diagonal matrices has recently been proposed by Srivastava and Du (2008) under the normal distribution and Srivastava (2009) under non-normality. It may be noted that this test is not invariant under the transformation by orthogonal matrices.…”
Section: Introductionmentioning
confidence: 99%